Study on the Effectiveness of CO2 Absorption in Biogas Purification Using Bittern and Alkaline Solutions - Hafiza, Putri Nur; Amalia, Felisa Rizky; Suprihatin; Pujiastuti, Caecilia; Triana, Nurul Widji (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Biogas is a renewable energy source with great potential to replace fossil fuels; however, the presence of CO? and H?S reduces its quality and combustion efficiency, making purification necessary. This study aimed to evaluate the effectiveness of CO? absorption using Bittern and alkaline solutions (3N KOH, 3N NaOH) with absorbent volumes ranging from 600 to 1000 ml. The absorption process was carried out in a bubble column, and the gas composition was analyzed using an Orsat apparatus and titration method. The results indicated that increasing absorbent volume reduced CO? concentration to 10–15% and H?S to below 1.2%, while increasing CH? content to more than 80%, in accordance with SNI 8019:2014 biogas standards. Stepwise absorption (Bittern–KOH/NaOH) was more effective than single absorbents, yielding up to 87% CH? and reducing CO? to 10%. XRF analysis of the precipitate showed calcium (84.58%) and magnesium (14%) dominance, confirming carbonate and sulfate precipitation. These findings demonstrate that Bittern and alkaline solutions are effective absorbents for biogas purification, with stepwise absorption providing the most optimal improvement in biogas quality. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 13: Climate Action